OP0190 The role of nsaids in the association between osteoarthritis and cardiovascular diseases: a population-based cohort study. (12th June 2018) - Atiquzzaman, M.; Kopec, J.; Karim, M.E.; Wong, H.; Anis, A.
Abstract : Background: Worldwide, osteoarthritis (OA) is a major musculoskeletal disorder. Recent research suggests that OA is an independent risk factor for cardiovascular disease (CVD). 1 The relationship is complicated because non-steroidal anti-inflammatory drugs (NSAIDs), a proven risk factor for CVD, are frequently used for the treatment of OA. 2 Researchers have hypothesised that NSAID use in the causal pathway between OA and CVD is what may ultimately impact these patients to develop CVD, this pathway has yet to be studied. 3, 4 Objectives: The objective of this study was to disentangle the role of NSAID in the increased risk of CVD among OA patients. Methods: This longitudinal study was based on linked health administrative data from British Columbia, Canada. From a population-based cohort of 720, 055 British Columbians, we matched on age and sex to assemble 7, 743 OA patients and 23 229 non-OA controls (1:3 ratio). We used multivariable Cox proportional hazards models to estimate the risk of developing incident CVD (primary outcome) as well as ischaemic heart disease (IHD), congestive heart failure (CHF) and stroke (secondary outcomes). To estimate the mediating effect of NSAIDs, defined as current use of NSAID using linked prescription dispensing records, in the OA-CVD relationship, we implemented a marginal structural model. Results: People with OA had 23% higher risk of developing CVD compared to people without OA after adjusting for SES, BMI, hypertension, diabetes, hyperlipidemia, COPD, and Romano comorbidity score, adjusted HR (95% CI) was 1.23 (1.17, 1.29). Adjusted HR (95% CI) was 1.42 (1.33, 1.52), 1.17 (1.10, 1.27), 1.14 (1.08, 1.24) for CHF, IHD and stroke, respectively. Approximately 67.51% of the total effect of OA on the increased risk of CVD was mediated through current NSAID use. Among the secondary outcomes, approximately 44.77% of increased CHF risk was mediated through current NSAID use. More than 90% of the total effects on IHD and stroke was mediated through the current NSAID use. Conclusions: Our study is the first to evaluate the mediating role of NSAID use in the OA-CVD relationship based on population-based health administrative data. The results of this study also indicate that OA is an independent risk factor for CVD. Our findings suggest that the mediating role of NSAID use substantially contributes to the OA-CVD association. References: [1] Wang H, Bai J, He B, Hu X, Liu D. Osteoarthritis and the risk of cardiovascular disease: A meta-analysis of observational studies. Sci Rep [Internet] 2016Dec [cited 2017 Sep 6];6(1). Available from http://www.nature.com/articles/srep39672 [2] Trelle S, Reichenbach S, Wandel S, Hildebrand P, Tschannen B, Villiger PM, et al. Cardiovascular safety of non-steroidal anti-inflammatory drugs: network meta-analysis. BMJ. 2011Jan 11;342:c7086. [3] Rahman MM, Kopec JA, Anis AH, Cibere J, Goldsmith CH. Risk of Cardiovascular Disease in Patients With Osteoarthritis: A Prospective Longitudinal Study: Cardiovascular Disease in Osteoarthritis Patients. Arthritis Care Res. 2013Dec;65(12):1951–8. [4] Link Between OAand CVD Risk [Internet]. arthritis.org. [cited 2017 Oct 23]. Available from: http://www.arthritis.org/living-with-arthritis/comorbidities/heart-disease/osteoarthritis-ups-cvd-risk.php Disclosure of Interest: None declared